Cabozantinib: a MET, RET, and VEGFR2 tyrosine kinase inhibitor - Grüllich, Carsten (Small molecules in oncology, 2014)
Cabozantinib is a receptor tyrosine kinase inhibitor with activity against MET, VEGFR2, FLT3, c-KIT, and RET. Activity of cabozantinib toward a broad range of tumor models could be detected in several preclinical studies. Of note, cabozantinib decreases metastasis potential and tumor invasiveness when compared with placebo or agents that target VEGFR and have no activity against MET. Clinical phase I and II studies with cabozantinib have been conducted in various malignancies including medullary thyroid cancer (MTC), NSCLC, breast, ovarian, pancreatic, and prostate cancer. In MTC, gain of function mutations of RET are central for tumorigenesis. Hereditary forms of MTC (MEN II) are caused by germline mutations of RET, in sporadic MTC in up to 50 % of cases RET mutations occur. Additionally, activating molecular changes in VEGFR and MET pathways have also been implicated in MTC progression. Clinical responses with cabozantinib in MTC could be observed in early clinical trials, and following confirmation of clinical benefit in a randomized phase III trial, cabozantinib gained FDA approval for first-line treatment of advanced MTC in 2012. In prostate cancer models, MET expression increases with androgen ablation and clinical progression of bone and lymph node metastasis. A phase II trial with cabozantinib also showed very promising response rates in patients with metastatic prostate cancer. Therefore, randomized phase III studies are currently ongoing to validate the efficacy of cabozantinib in heavily pretreated prostate cancer patients.